Radiation-Induced Senescence Bystander Effect: The Role of Exosomes - Elbakrawy, Eman (Biology (Basel), 2020)
Ionizing Radiation (IR), especially at high doses, induces cellular senescence in exposed cultures. IR also induces “bystander effects” through signals released from irradiated cells, and these effects include many of the same outcomes observed following direct exposure. Here, we investigate if radiation can cause senescence through a bystander mechanism. Control cultures were exposed directly to 0, 0.1, 2, and 10 Gy. Unirradiated cells were treated with medium from irradiated cultures or with exosomes extracted from irradiated medium. The level of senescence was determined post-treatment (24 h, 15 days, 30 days, and 45 days) by β-galactosidase staining. Media from cultures exposed to all four doses, and exosomes from these cultures, induced significant senescence in recipient cultures. Senescence levels were initially low at the earliest timepoint, and peaked at 15 days, and then decreased with further passaging. These results demonstrate that senescence is inducible through a bystander mechanism. As with other bystander effects, bystander senescence was induced by a low radiation dose. However, unlike other bystander effects, cultures recovered from bystander senescence after repeated passaging. Bystander senescence may be a potentially significant effect of exposure to IR, and may have both beneficial and harmful effects in the context of radiotherapy.